2020
DOI: 10.15376/biores.16.1.236-248
|View full text |Cite
|
Sign up to set email alerts
|

The durability of press-formed paperboard trays – Effects of sealing and drying

Abstract: Dimensional measurements were recorded to observe the durability of press-formed paperboard trays used for food processing via heating and cooling of the paperboard trays containing oatmeal. A set of the studied press-formed paperboard trays were dried before being heated, and a set of the paperboard trays were heat-sealed before being cooled to compare the effects of drying and sealing on the durability of the tray. In addition, empty trays were heated to observe the impact of food processing conditions on it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
(11 reference statements)
1
3
0
Order By: Relevance
“…The measured moisture content of the trays was 7.5% after the storing tests, which was greater than the 6.3% recorded before the trays were stored. Consistent with the previous work (Niini et al 2021), the material response to the moisture absorption was observed as a flange distortion on the longer sides of the tray (Figs. 12 and 13).…”
Section: Storing Testssupporting
confidence: 91%
See 3 more Smart Citations
“…The measured moisture content of the trays was 7.5% after the storing tests, which was greater than the 6.3% recorded before the trays were stored. Consistent with the previous work (Niini et al 2021), the material response to the moisture absorption was observed as a flange distortion on the longer sides of the tray (Figs. 12 and 13).…”
Section: Storing Testssupporting
confidence: 91%
“…Humidity exposure can lead to stiffness degradation and dimensional instability of paperboard, limiting the use of paperboard trays in moist environments typical to the production and storing of food packages. The drying and heat-sealing of paperboard trays improved the dimensional stability in a previous work (Niini et al 2021), yet the negative humidity effect to the tray rigidity was not eliminated. The humidity exposure yields creep deformation in tray packages, and cyclic humidity conditions aggravate the creep (Sørensen and Hoffmann 2004).…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations